Optimization of Ultrasonic-Assisted Extraction of Flavonoids from Fenugreek Using Response Surface Methodology and High-Performance Liquid Chromatography-Diode Array Detector Coupled with Mass Spectrometry Analysis - Yang, Renming; Wang, Honglun; Li, Gang; Suo, Yourui; You, Jinmao (Asian Journal of Chemistry, 2014)
In this study, a central composite design based on response surface methodology was used to optimize ultrasonic-assistant extraction of flavonoids from Trigonella foenum-graecum L. The optimal conditions to obtain the highest yield of total flavonoids were as follows: ultrasonic time of 80 min, temperature of 48 °C and liquid to solid ratio of 20 g/mL, where 1.03 % yield was predicted. After extraction process optimization, a method for the analysis of flavonoids in Trigonella foenum-graecum L. by HPLC-DAD-MS was developed. The LOD and LOQ of these 4 compounds range from 50.94 to 70.31 ng/mL and 179.63 to 208.85 ng/mL, respectively. The established HPLC-DAD-MS method was proven to be useful for the quantitative and qualitative analysis of flavonoid constituents in fenugreek seed. This is the first report on preparation, identification and determination of flavonoids in fenugreek seed by different method and which would provide a basis for medicinal and edible use of fenugreek.